2021
DOI: 10.2196/23592
|View full text |Cite
|
Sign up to set email alerts
|

A Text Messaging Intervention for Coping With Social Distancing During COVID-19 (StayWell at Home): Protocol for a Randomized Controlled Trial

Abstract: Background Social distancing is a crucial intervention to slow down person-to-person transmission of COVID-19. However, social distancing has negative consequences, including increases in depression and anxiety. Digital interventions, such as text messaging, can provide accessible support on a population-wide scale. We developed text messages in English and Spanish to help individuals manage their depressive mood and anxiety during the COVID-19 pandemic. Objective In a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…Our success in reducing COVID-19 transmission relies on people voluntarily adopting prevention behaviors. A number of studies have investigated messaging strategies that have potential in promoting preventive behaviors in response to COVID-19 (Everett et al, n.d.;Figueroa et al, 2021;Hacquin et al, 2020;Ma & Miller, 2021;Pink et al, 2020;Sobande, 2020). The current study highlights the importance of considering culture when designing such messages.…”
Section: Discussionmentioning
confidence: 80%
“…Our success in reducing COVID-19 transmission relies on people voluntarily adopting prevention behaviors. A number of studies have investigated messaging strategies that have potential in promoting preventive behaviors in response to COVID-19 (Everett et al, n.d.;Figueroa et al, 2021;Hacquin et al, 2020;Ma & Miller, 2021;Pink et al, 2020;Sobande, 2020). The current study highlights the importance of considering culture when designing such messages.…”
Section: Discussionmentioning
confidence: 80%
“…Importantly, the content is pre-established, not sent by a live therapist, and not tailored to each user. More information on the study protocol can be found in previous work ( Figueroa et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The sample size calculation was performed in a previous protocol paper [23], which includes 2 aims. This paper only considers the primary aim.…”
Section: Power Analysismentioning
confidence: 99%
“…Further studies are needed to compare the effectiveness of personalizing messages using a reinforcement learning algorithm to that of a random message condition. Other studies in progress may be better suited to answer questions related to the impact of reinforcement learning models' utility for improving personalization [23].…”
Section: Principal Findingsmentioning
confidence: 99%
See 1 more Smart Citation